Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1439-0396.1993.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary crude protein level on amino acid digestibility in early‐weaned pigs

Abstract: AnimalsFourteen pigs (Yorkshire x Landrace), weaned at 3 weeks of age, were obtained from the University of Alberta swine herd. The pigs were housed individually in metabolic crates (height: 85 cm; length: 70 cm; width: 65 cm) in a barn with automatic temperature control (25 to 28" C) and fed an 18% crude protein starter diet (SAUER et al. 1983) adlibitum. Water was freely available from a low-pressure drinking nipple.The pigs were fitted with a simple T-cannula at the distal ileum on d 2 and 3 after weaning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 14 publications
5
60
0
Order By: Relevance
“…Of the indispensable AA, the differences ranged from 1.9 percentage units for arginine to 3.3 percentage units for threonine. Similar results were found by Li et al (1993). In confrast, experimental period did not affect (P > 0.05) the apparent fecal digestiblities of AA.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Of the indispensable AA, the differences ranged from 1.9 percentage units for arginine to 3.3 percentage units for threonine. Similar results were found by Li et al (1993). In confrast, experimental period did not affect (P > 0.05) the apparent fecal digestiblities of AA.…”
Section: Resultssupporting
confidence: 78%
“…The pigs were fitted with a simple T-cannula at the distal ileum on day 6 and day 7 after weaning. Detailed descriptions of the preparation of the cannulas and pre-and postoperative care were provided by Li et al (1993) and (Gaberl et al 1995) andO.2O7o mineral premix (Gabert et al 1995 During the experiment, the pigs were fed at 0600, 1400 and 2200 h. Daily feed allowance was 4Vo of BW and was based on the BW ofpigs on the day before the start ofeach experimental period. The average feed intake was 348 t 28 g d-r during period I and425 t 38 g d-l during period 2.…”
mentioning
confidence: 99%
“…AmiPig, 2000;GfE, 2008;Rademacher et al, 2009), but are also used in diet formulation for nursery pigs. However, Li et al (1993) reported in early weaned pigs a significant increase in ileal AA digestibilities with age and proposed that piglets may have a limited capacity for CP digestion and AA absorption. In addition, factors such as body weight (BW) and age (Caine et al, 1997a and1997b), and the level of feed intake (Moter and Stein, 2004;Diebold et al, 2005) may affect AID and IAAL B in piglets.…”
Section: Introductionmentioning
confidence: 99%
“…The collection procedure was adapted from Li et al (1993) using plastic tubing attached to the barrel of the cannula by elastic bands. The bags were changed at least every 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The pigs were fitted with simple T-cannulas at the distal ileum according to the principles described by Li et al (1993). They were kept individually in stainless steel metabolic crates.…”
Section: Animals and Housingmentioning
confidence: 99%